2010
DOI: 10.1103/physrevb.82.212505
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and structural isotope effects in iron-based superconductors

Abstract: The currently available results of the isotope effect on the superconducting transition temperature Tc in Fe-based high-temperature superconductors (HTSs) are highly controversial. The values of the Fe isotope effect exponent Fe for various families of Fe-based HTS were found to be as well positive, as negative, or even be exceedingly larger than the BCS value BCS 0.5. Here we emphasize that the Fe isotope substitution causes small structural modifications which, in turn, affect Tc. Upon correcting the isotope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
(67 reference statements)
0
20
2
1
Order By: Relevance
“…We note that the estimated value is much higher than the iron isotope coefficient calculated using T c on the SmFeAsO 0.77 H 0.12 system. 48 Khasanov et al, 50 pointed out that isotope substitution in these systems causes a small structural modification and that inturn affects T c . They did a detailed analysis of the existing studies on the iron-isotope effect using T c and found that the intrinsic isotope effect, which is independent of structural changes, in all of these systems is consistent and of the order of ∼ 0.35 -0.4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the estimated value is much higher than the iron isotope coefficient calculated using T c on the SmFeAsO 0.77 H 0.12 system. 48 Khasanov et al, 50 pointed out that isotope substitution in these systems causes a small structural modification and that inturn affects T c . They did a detailed analysis of the existing studies on the iron-isotope effect using T c and found that the intrinsic isotope effect, which is independent of structural changes, in all of these systems is consistent and of the order of ∼ 0.35 -0.4.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the electronphonon strength in FeBS is compared to that in MgBr 2 superconductor, where the superconductivity is mediated by electron-phonon coupling. In addition to these theoretical calculations, a large isotope coefficient as high as α Fe ∼ 0.81 has been reported experimentally for different families of FeBS, [46][47][48][49][50][51][52] clearly suggesting that the electron-phonon coupling can not be ruled out in understanding the pairing mechanism in these materials along with other degrees of freedom such as spin and orbital.…”
Section: Introductionmentioning
confidence: 89%
“…Upon the application of pressure, its T c increases up to 37 K at p ~ 7 GPa 9 10 . Although there are experimental and theoretical studies showing the unconventional superconductivity in the FeSCs 11 12 13 14 15 , the Fe isotope effect has been observed 16 17 18 19 20 which implies the role of phonons may not be sorely excluded. On the other hand, SnO is comprised of nonmagnetic atoms so magnetism-related mechanism can not account for the electron pairing in SnO.…”
mentioning
confidence: 99%
“…However, his approach has been questioned by Bussmann-Holder and Keller12 that claimed that an inversion of the Fe-IE exponent could not occur. More recently, Khasanov et al 13 tried solving the discrepancy in the Fe-IE measurements by decomposing the exponent in two terms: one associated to structural changes and one intrinsic. They also pointed out that the Fe isotope substitution may induce small structural changes which, in turn, may affect T c .…”
mentioning
confidence: 99%